2015
DOI: 10.1093/chemse/bjv019
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Mental Retardation Protein Regulates Olfactory Sensitivity But Not Odorant Discrimination

Abstract: Fragile X syndrome (FXS) is the most common cause of inherited intellectual disability and is characterized by cognitive impairments and altered sensory function. It is caused by absence of fragile X mental retardation protein (FMRP), an RNA-binding protein essential for normal synaptic plasticity and function. Animal models have provided important insights into mechanisms through which loss of FMRP impacts cognitive and sensory development and function. While FMRP is highly enriched in the developing and adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In contrast, Fmr1 -/y mice (20) did not learn to discriminate the two odorants after a 10day enrichment period ( Fig.1D and supplementary Fig.S1C). This was not due to a general olfactory discrimination defect of the knocked-out (KO) mice since they spontaneously discriminated two perceptually distinct odorants (Octanal/Carvone, supplementary Fig.S1D) and as previously described (21). This suggests that FMRP is necessary for the perceptual learning underlying discrimination of similar odorants.…”
Section: Fmrp In Adult-born Neurons Is Necessary For Olfactory Percepsupporting
confidence: 76%
“…In contrast, Fmr1 -/y mice (20) did not learn to discriminate the two odorants after a 10day enrichment period ( Fig.1D and supplementary Fig.S1C). This was not due to a general olfactory discrimination defect of the knocked-out (KO) mice since they spontaneously discriminated two perceptually distinct odorants (Octanal/Carvone, supplementary Fig.S1D) and as previously described (21). This suggests that FMRP is necessary for the perceptual learning underlying discrimination of similar odorants.…”
Section: Fmrp In Adult-born Neurons Is Necessary For Olfactory Percepsupporting
confidence: 76%
“…Neurosensorial abnormalities are a strong phenotype of the FXS conditions. Indeed, odorant sensitivity (Schilit Nitenson et al, 2015) and nociceptive responses after a local acute inflammation (Price et al, 2007; Busquets-Garcia et al, 2013) are significantly lower in the FXS model whereas an excessive excitability of auditory processing (Garcia-Pino et al, 2017) and an exaggerated response to whisker stimulation (He et al, 2017) were observed. Regarding vision, few data were reported and they were associated to cognitive mechanism such as the Fmr1 −/y delayed learning on visual discrimination tasks (Goel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hypersensitivity phenotypes have been demonstrated for audition aspects as well as for visual responses since Fmr1 −/y mice present hyper arousal excitability for auditory processing and exacerbated transmission between photoreceptors and the inner retina (as observed in our experiment), respectively. But tactile nociception after local acute inflammation is lowered (Price et al, 2007 ; Busquets-Garcia et al, 2013 ), and Fmr1 −/y mice present a significant decrease in odorant sensitivity (Schilit Nitenson et al, 2015 ). Consequently, we propose that the most relevant terminology to characterize this complex sensorial spectrum is “dys-sensitivity phenotype” instead of “hyper-sensitivity phenotype”.…”
Section: Discussionmentioning
confidence: 99%